BIBLIOMETRIC ANALYSIS AND VISUALIZATION OF CROWDFUNDING ARTICLES INDEXED IN SCOPUS BY INDONESIAN AUTHORS - Deasy Tantriana (Yayasan Education and Social Center, 2023)
This study aimed to analyze the bibliometric characteristics and trends of articles on crowdfunding indexed in Scopus by Indonesian authors. Information was taken from the Scopus database. In March 2023, reports were only searched if they had Indonesian authors or affiliations. This study used crowdfunding and its variations as search terms, with Indonesian affiliation being considered. Simple statistical techniques were applied, and VOSviewer software was used to perform a bibliometric analysis. This study visualized patterns of keyword co-occurrence, document citations, co-citation relationships, and bibliographic coupling. Indonesian authors' research in the area of crowdfunding has expanded quickly and with much cooperation. One of the most well-liked study areas in recent years is Website crowdfunding development. The credibility of crowdfunding ini Indonesia has recently gained popularity, which presents a significant opportunity for additional research